Optimizing the Role of Production Assistants: The Key to Production Efficiency in the 'Food Diary' Program on iNews - Rahayu, Khairunnisa; Suparman (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
This study discusses the optimization of the role of Production Assistants (PAs) in improving the production efficiency of the